Back to the future: Using prophecy to support Māori student success in tertiary education - Rangiwai, Byron (Te Kaharoa, 2021)
Māori view time differently to Pākehā. Mahuika (2010) argues that the concept of walking backwards into the future is a common one for Māori and other Polynesian peoples. According to Roberts (2005): “It is often said that Māori are a people who “walk backwards into the future,” an aphorism that highlights the importance of seeking to understand the present and make informed decisions about the future through reference to the past” (p. 8). This paper will argue that it is critical for Māori to walk backwards into the future and that our prophecies can be used to support Māori student success in tertiary education.